2021
DOI: 10.1038/s41522-021-00242-3
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and metabolites of α-synuclein transgenic monkey models with early stage of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease. However, it is unclear whether microbiota and metabolites have demonstrated changes at early PD due to the difficulties in diagnosis and identification of early PD in clinical practice. In a previous study, we generated A53T transgenic monkeys with early Parkinson’s symptoms, including anxiety and cognitive impairment. Here we analyzed the gut microbiota by metagenomic sequencing and metabolites by targeted gas chromatography. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Various studies over the past few decades have observed distinct differences in microbiota composition between individuals with and without PD, as well as between individuals with different PD phenotypes of symptomology (Heintz-Buschart et al, 2018;Heinzel et al, 2021). A recent study observed differences in the microbiota (elevated Akkermansia, Eggerthella, and Synergistetes; depleted Prevotella) between A53T transgenic monkeys with early-stage PD and control monkeys (Yan et al, 2021a). These results extend upon commonly observed microbiota differences between human PD patients and healthy controls to an earlier timepoint of disease progression.…”
Section: Microbiota Composition and Metabolites Associated With Parkinson's Disease And Symptom Severitymentioning
confidence: 99%
“…Various studies over the past few decades have observed distinct differences in microbiota composition between individuals with and without PD, as well as between individuals with different PD phenotypes of symptomology (Heintz-Buschart et al, 2018;Heinzel et al, 2021). A recent study observed differences in the microbiota (elevated Akkermansia, Eggerthella, and Synergistetes; depleted Prevotella) between A53T transgenic monkeys with early-stage PD and control monkeys (Yan et al, 2021a). These results extend upon commonly observed microbiota differences between human PD patients and healthy controls to an earlier timepoint of disease progression.…”
Section: Microbiota Composition and Metabolites Associated With Parkinson's Disease And Symptom Severitymentioning
confidence: 99%
“…The genus Akkermansia is consistently enriched in human PD patients versus healthy controls, and the data corroborate recent findings in an A53T α-synuclein Tg non-human primate model. Investigators noted a higher diversity of microbial flora with significant increases in abundance of Akkermansia, Sybergistetes, and Eggerthella lenta (Nishiwaki et al, 2020;Yan et al, 2021). As a mucin-degrading bacteria, Akkermansia spp.…”
Section: Gut Microbiome-mediated Fibril Formationmentioning
confidence: 99%
“…diet, impact the gut microbiome (Bernardo-Cravo et al 2020;Singh et al 2019). Changes in gut microbial composition in PD has been described extensively in humans (Boertien et al 2019;Gerhardt and Mohajeri 2018;Heintz-Buschart et al 2018;Keshavarzian et al 2015;Scheperjans et al 2015;Shen et al 2021;Unger et al 2016), but also more and more in different animal models (Gorecki et al 2019;Sampson et al 2016;Yan et al 2021). Using 16S rRNA amplicon sequencing, our goal was to understand how the disease challenges affected, independently or in combination, the microbial phenotype in our mice.…”
Section: Translationally Relevant Pd-like Microbial Changes Induced A...mentioning
confidence: 99%